Social Facilitation of Laughter and Smiles in Preschool Children - Addyman, Caspar; Fogelquist, Charlotte; Levakova, Lenka; Rees, Sarah (Frontiers in Psychology, 2018)
Surprisingly little is known about the social dimensions of laughter in preschool children. We studied children’s responses to amusing video clips in the presence or absence of peers. The sample consisted of 9 boys and 11 girls aged 31–49 months (M 39.8, SD 4.2) who watched three cartoons under three different conditions: individually, in pairs, or in groups of 6 or 8. The social viewing conditions showed significantly higher numbers of laughs and smiles than the individual viewing condition. On average children laughed eight times as much in company as on their own and smiled almost three times as much. No differences were found between pairs and groups, and no association was found between subjective funniness ratings and group size. This suggests that the presence of even a single social partner can change behavior in response to humorous material. It supports the idea that laughter and smiles are primarily flexible social signals rather than reflexive responses to humor.